Analysis of simulated annealing based optimization of human movement for performance enhancement - Gupta, D.; Jensen, J. L.; Abraham, L. (ISBS Proceedings Archive (Michigan), 2017)
Technique is a defining feature of success in sport performance. In aerial phases of sport skills, in particular, it is the interplay among articulated body segments that optimizes the outcome. This interplay is characterized by intersegmental interactions during the projectile trajectory, the aerial phase, of the body`s center of mass. The purpose of this study was to examine mathematical optimization approaches to finding the best balance of intersegmental interaction and in that process maximizing the desired performance outcome. We compared optimization using two different search algorithms, brute-force and simulated annealing and found that using simulated annealing is an efficient way to search for optimal solutions for biomechanical problems.